Atypical Presentations of Rheumatoid Arthritis (KYAMC Journal, 2017)
Rheumatoid Arthritis is a common rheumatological problem. It may involve many extra articular organic systems along with joints. Disability resulting from progressive Rheumatoid Arthritis has an enormous effect on our society and it is a drain for human as well as monetary resources. About half of all patients with Rheumatoid Arthritis stop working by 10 years, 90% by 30 years. Disability may be due to both to obvious limitation of joint destruction and pain to complication of therapy and to extra articular problems of Rheumatoid Arthritis, it also shortens life significantly. As inflammatory chronic poly-arthritis, most of the cases of Rheumatoid Arthritis present with constitutional symptoms with typical presentation but a group of patients may produce difficulties for diagnosis due to a variety of atypical presentations. Knowledge about atypical presentations & onset of rheumatoid arthritis is very important to prevent disabling complications of rheumatoid arthritis resulting from joint failure as well as from non musculoskeletal involvement.KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 587-591